Peran Brand Trust dalam Memediasi Pengaruh Product Quality dan Brand Image terhadap Loyalitas Konsumen Laptop ASUS di Kota Semarang - Ahmed Azril Syah Zuhri; Heru Sulistyo (Lembaga Yasin AlSys, 2026)
Intensifying competition in the laptop industry requires companies to maintain consumer loyalty as a key factor for business sustainability. In this context, ASUS, as one of the leading laptop brands in Indonesia, needs to pay close attention to factors influencing consumer loyalty, particularly product quality and brand image, with brand trust as a mediating variable. This study aimed to analyze the effect of product quality and brand image on consumer loyalty through brand trust among ASUS laptop users in Semarang City. A quantitative approach was employed, with primary data collected through questionnaires administered to 100 respondents. The data were analyzed using Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) approach. The results showed that product quality and brand image had a positive and significant effect on brand trust. Furthermore, brand trust had a positive and significant effect on consumer loyalty and was able to mediate the influence of product quality and brand image on consumer loyalty. These findings affirm that improving product quality and strengthening brand image contribute to reinforcing consumer trust, which ultimately enhances brand loyalty. The implications of this study offer theoretical contributions to the development of trust-based marketing studies and practical considerations for companies in designing marketing strategies oriented toward the formation and maintenance of brand trust.